Fall of Hypocritical Aristocrats in Anton Chekov’s The Cherry Orchard (SNPRC Journal, 2025)
This research paper explores on the liberation of serfs in Russia by exemplifying the life of the protagonist, Lopakhin, of Anton Chekov’s play, The Cherry Orchard. Lopakhin resembles the every the then Russian serf. He has the idealistic journey of evolution, emancipation from the serfdom to eventually becoming an estate owner. His transformation voices the Russian peasants’ revolution after their suffering of almost two hundred years. By using the class struggles theory of USSR, giving the special touch of Socialism, this paper tries to investigate on the issue of serf exploitation, their revolution and their eventual liberation from the aristocrats. Ranevsky, the aristocrat of this drama is an example of those corrupted nobles of eighteenth century of Russia. Her ruin is ultimate destruction of aristocrats clearing the path for benevolent peasants. The rise of Lopakhin speaks the genesis of democracy in Russia. This research paper primarily depends on the theories of Karl Marx, Fredrick Engels, VI Lenin and other socio-economic revolutionary theories to justify the socio-economic revolution that emancipates the two hundred years of slavery in Russia.